2018
DOI: 10.1111/jbi.13220
|View full text |Cite
|
Sign up to set email alerts
|

Range‐constrained co‐occurrence simulation reveals little niche partitioning among rock‐dwelling Montenegrina land snails (Gastropoda: Clausiliidae)

Abstract: AimTaxon co-occurrence analysis is commonly used in ecology, but it has not been applied to range-wide distribution data of partly allopatric taxa because existing methods cannot differentiate between distribution-related effects and taxon interactions. Our first aim was to develop a taxon co-occurrence analysis method that is also capable of taking into account the effect of species ranges and can handle faunistic records from museum databases or biodiversity inventories. Our second aim was to test the indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
(62 reference statements)
0
21
0
Order By: Relevance
“…The overall topology of the DNA‐based tree was already introduced by Fehér et al. (2018). Mason et al.…”
Section: Introductionmentioning
confidence: 99%
“…The overall topology of the DNA‐based tree was already introduced by Fehér et al. (2018). Mason et al.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive radiations, which are the result of ecological speciation by divergent selection and a rapid adaptation of incipient species to different niches, have been studied in detail, for example the Darwin's finches in the Galápagos Islands (Grant & Grant, ), Anolis lizards of the Caribbean (Losos, ) or cichlid fish in Africa (Seehausen, ). In contrast, non‐adaptive radiations, in which diversification is not accompanied by adaptation into different niches, but results in a group of usually allopatric species occupying similar niches (Dominey, ; Fehér et al, ; Gittenberger, ; Rundell & Price, ) have been neglected for a long time. However, the importance of non‐adaptive radiations may be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that early phylogenetic divergence in rock-dwelling door snails is driven primarily by non-adaptive factors (Fehér et al, 2018). As there is no reason to assume that one of the chiral directions in Cristataria would be more advantageous than the other, it seems reasonable assuming that a reversed phenotype become fixed in a small, spatially isolated population once its frequency exceeded 50% (van Batenburg & Gittenberger, 1996;Orr, 1991;Ueshima & Asami, 2003) and not because of any survival/reproductive advantage (Hoso et al, 2010;Johnson, Murray, & Clarke, 1993).…”
Section: Discussionmentioning
confidence: 99%